DOI: 10.33915/etd.3473
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized Cytochrome P450 2C9 (CYP2C9): Applications for Metabolite Generation, Monitoring Protein-Protein Interactions, and Improving In-vivo Predictions Using Enhanced In-vitro Models

Abstract: Development of Au-Immobilized P450 Platform for Exploring the Effect of Oligomer Formation on P450-Mediated Metabolism for In Vitro to In Vivo Drug Metabolism Predictions Lance A. Wollenberg Cytochrome P450 (P450) enzymes are a family of oxoferroreductase enzymes containing a heme moiety and are well known to be involved in the metabolism of a wide variety of endogenous and xenobiotic materials. It is estimated that roughly 75% of all pharmaceutical compounds are metabolized by these enzymes. Traditional recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 176 publications
0
2
0
Order By: Relevance
“…381 However, Raman shifts were also observed, indicative of the inactive form, and it was not possible to reduce the protein heme group. This result is interesting given recent work, which demonstrated that biologically active CYP2D6 can be adsorbed via a SAM on Au, 382 and may reveal surface-specific differences in immobilized P450 function. Surface plasmon resonance (SPR) spectroscopy has been successfully used to study multi-layer /aggregation formation during immobilization (Figure 16).…”
Section: Measuring Protein Adsorption and Functionality Onmentioning
confidence: 74%
See 1 more Smart Citation
“…381 However, Raman shifts were also observed, indicative of the inactive form, and it was not possible to reduce the protein heme group. This result is interesting given recent work, which demonstrated that biologically active CYP2D6 can be adsorbed via a SAM on Au, 382 and may reveal surface-specific differences in immobilized P450 function. Surface plasmon resonance (SPR) spectroscopy has been successfully used to study multi-layer /aggregation formation during immobilization (Figure 16).…”
Section: Measuring Protein Adsorption and Functionality Onmentioning
confidence: 74%
“…However, Raman shifts were also observed, indicative of the inactive form, and it was not possible to reduce the protein's heme group. This result is interesting given recent work, which demonstrated that biologically active CYP2D6 can be adsorbed via a SAM on Au [377], and may reveal surface-specific differences in immobilized P450 function.…”
Section: Measuring Protein Adsorption and Functionality On A Surfacementioning
confidence: 75%